THE ROLE OF AMIR TEMUR IN THE HISTORY OF UZBEKISTAN AND THE WORLD - Axmedova O`G`Iloy Ismoil Qizi (International Journal Of History And Political Sciences, 2023)
In this article, Amir TEMUR, a great general and patron of science, who established a great kingdom in his time, took a worthy place in Uzbek statehood and world history, and the place and role of Temur in Uzbekistan and World historiography is talked about. Some information about the fact that he left an indelible mark in history as the ruler of the state and patron of science, and about the scientific researches that studied Sahibqiran and its history in world history.